Depletion of soil carbon and aggregation after strong warming of a subarctic Andosol under forest and grassland cover - Poeplau, Christopher; Sigurðsson, Páll; Sigurdsson, Bjarni D. (SOIL, 2020)
The net loss of soil organic carbon (SOC) from terrestrial ecosystems is a likely consequence of global warming and may affect key soil functions. The strongest changes in temperature are expected to occur at high northern latitudes, with forest and tundra as prevailing land cover types. However, specific soil responses to warming in different ecosystems are currently understudied. In this study, we used a natural geothermal soil warming gradient (0–17.5 ∘ C warming intensity) in an Icelandic spruce forest on Andosol to assess changes in the SOC content between 0 and 10 cm (topsoil) and between 20 and 30 cm (subsoil) after 10 years of soil warming. Five different SOC fractions were isolated, and their redistribution and the amount of stable aggregates were assessed to link SOC to changes in the soil structure. The results were compared to an adjacent, previously investigated warmed grassland. Soil warming depleted the SOC content in the forest soil by −2.7 g kg −1 ∘ C −1 ( −3.6 % ∘ C −1 ) in the topsoil and −1.6 g kg −1 ∘ C −1 ( −4.5 % ∘ C −1 ) in the subsoil. The distribution of SOC in different fractions was significantly altered, with particulate organic matter and SOC in sand and stable aggregates being relatively depleted and SOC attached to silt and clay being relatively enriched in warmed soils. The major reason for this shift was aggregate breakdown: the topsoil aggregate mass proportion was reduced from 60.7±2.2 % in the unwarmed reference to 28.9±4.6 % in the most warmed soil. Across both depths, the loss of one unit of SOC caused a depletion of 4.5 units of aggregated soil, which strongly affected the bulk density (an R 2 value of 0.91 and p <0.001 when correlated with SOC, and an R 2 value of 0.51 and p <0.001 when correlated with soil mass in stable aggregates). The proportion of water-extractable carbon increased with decreasing aggregation, which might indicate an indirect protective effect of aggregates larger than 63 µ m on SOC. Topsoil changes in the total SOC content and fraction distribution were more pronounced in the forest than in the adjacent warmed grassland soils, due to higher and more labile initial SOC. However, no ecosystem effect was observed on the warming response of the subsoil SOC content and fraction distribution. Thus, whole profile differences across ecosystems might be small. Changes in the soil structure upon warming should be studied more deeply and taken into consideration when interpreting or modelling biotic responses to warming.